Whole-genome sequencing identified candidate genes associated with high and low litter size in Chuanzhong black goats - Guo, Conghui; Ye, Junning; Liu, Jie; Li, Zhihan; Deng, Ming; Guo, Yongqing; Liu, Guangbin; Sun, Baoli; Li, Yaokun; Liu, Dewu (Frontiers in Veterinary Science, 2024)
The reproductive performance of goats significantly influences breeding efficiency and economic returns, with litter size serving as a comprehensive indicator. Despite this, research on the genetic control of litter size remains limited. Therefore, we aimed to explore the candidate genes affecting fecundity and compared the whole-genome sequences (WGS) of 15 high-litter (HL) and 15 low-litter (LL) size in Chuanzhong black goats. Then genetic diversity and genomic variation patterns were analyzed by phylogenetic, principal component and population genetic structure analysis, it was found that HL and LL subpopulations diverged. Population evolutionary selection elimination analysis was performed by Fst and θπ resulted in 506 genes were annotated in HL and 528 genes in LL. These genes were mainly related to Hippo signaling pathway, G protein-coupled signaling pathway, G protein-coupled receptor activity, cell surface receptor signaling pathway, gonadal and reproductive structure development. According to the significantly selected genomic regions and important pathways, we found that the g.89172108T > G variant locus in the exon of the AMH gene was significantly associated with litter size (P < 0.05), which could be used as an auxiliary selection gene for the high fertility of Chuanzhong black Goat.